Report on General Issues Relating to Backward Areas Development - Planning Commission (Planning Commission, 1981)
The problem of regional balance and of backwardness has attracted the attention of planners. The problem has sometimes been seen in terms of inter-state disparities though there is also a recognition that there are many disparities within each slate also. The emphasis has been on backwardness in terms of economic performance though the impact of historical and social factors on economic matters has been recognised.
National Committee on the Development of Backward Areas, Planning Commission, Government of India